Promoter analysis of the gene encoding the I kappa B-alpha/MAD3 inhibitor of NF-kappa B: positive regulation by members of the rel/NF-kappa B family. - Le Bail, O (1993)
In order to characterize the regulation of the gene encoding the I kappa B-alpha/MAD3 inhibitor of the transcription factor NF-kappa B, we have isolated a human genomic clone and sequenced the promoter of this gene. The MAD3 promoter exhibits a potential TATA element upstream of one of the two major transcription sites, and contains several potential NF-kappa B binding sequences, suggesting that the gene is positively regulated by members of this family. Transfection experiments demonstrate that the MAD3 promoter can be activated by various combinations of members of the rel/NF-kappa B family, as well as by phorbol esters and tumor necrosis factor. Specific deletion of one of the kappa B motifs, located 37 bp upstream of the TATA box, abolishes responses to PMA and TNF. This kappa B motif binds NF-kappa B (p50/relA), p50/c-rel and relA/c-rel heterodimers as well as KBF1 (p50 homodimer). These results help to explain the previously observed transient nature of the NF-kappa B response: following NF-kappa B activation, the expression of the inhibitor is increased, therefore the extent of nuclear translocation of the active complex is reduced, resulting in a decreased activation of its target genes.